2018
DOI: 10.3748/wjg.v24.i42.4787
|View full text |Cite
|
Sign up to set email alerts
|

Mode of delivery by an ulcerative colitis mother in a case of twins: Immunological differences in cord blood and placenta

Abstract: AIMTo understand the effects of delivery mode on the immune cells frequency and function in cord blood and placenta.METHODSWe evaluated immunological differences in cord blood and placental tissues for a case of twins one of which delivered vaginally while the other delivered by caesarian section (C-section). Cord blood mononuclear cells were isolated and placenta tissues were processed for cell isolation. Immune phenotyping was performed by flow cytometry methods following staining for T cells, natural killer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Given the high surface expression of ACE2 and TMPRSS2 on placental CECs and their permissibility to ARS-CoV-2 infection, raises the possibility of vertical viral transmission seems possible. Also, CECs become abundant in the peripheral blood of pregnant women at the later stage of pregnancy 33,34,40 , which in part may support the reported viremia and placental transmission of SARS-CoV-2 60 . This was challenged due to negligible co-expression of ACE2 and TMPRSS2 by placental cell types 61 .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Given the high surface expression of ACE2 and TMPRSS2 on placental CECs and their permissibility to ARS-CoV-2 infection, raises the possibility of vertical viral transmission seems possible. Also, CECs become abundant in the peripheral blood of pregnant women at the later stage of pregnancy 33,34,40 , which in part may support the reported viremia and placental transmission of SARS-CoV-2 60 . This was challenged due to negligible co-expression of ACE2 and TMPRSS2 by placental cell types 61 .…”
Section: Discussionmentioning
confidence: 55%
“…6E and 6F). To examine the infectivity of CEC's obtained from a SARS-CoV2 naïve source we infected CECs isolated from human placenta with SARS-CoV2, because placenta is physiologically enriched with CECs 33,34,40,41 possessing ACE2 and TMPRSS2 (Fig. 3D, Fig.…”
Section: Cecs Get Infected With Sars-cov-2 and Dexamethasone Reduces mentioning
confidence: 99%
“…We found that the amount of viral RNA in CECs and produced by CECs was similar to monocytes ( Figures 6 E and 6F). To examine the infectivity of CECs obtained from a SARS-CoV2-naive source we infected CECs isolated from human placenta with SARS-CoV2, because placenta is physiologically enriched with CECs ( Delyea et al., 2018 ; Dunsmore et al., 2018a , 2018b ; Gomez-Lopez et al., 2016 ), possessing ACE2 and TMPRSS2 ( Figures 3 D and 5 G). Similar to CECs from COVID-19 patients, placental CD45 + CECs had substantial surface expression of ACE2 ( Figures S6 A and S6B) and TMPRSS2 ( Figure S6 C).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, not only was the frequency of CEC observed in the cord blood and placenta of a twin delivered by Cesarean section lower than that of the vaginally delivered twin, but the CEC of the two twins also had a different gene profile. 27 It can, therefore, be speculated that lower levels of CEC in IBD patients may result in intestinal dysbiosis and poor pregnancy outcomes. 28,29 In support of this hypothesis, lower CEC frequency was associated with preterm deliveries and emergency Cesarean sections.…”
Section: Immunological Benefits Of Extramedullary Erythropoiesis In Pmentioning
confidence: 99%